Analisis Tingkat Persepsi Mahasiswa Uin Terhadap Penggunaan Transportasi Online (Gojek, Grab, Indrive, Dan Maxim) Sebagai Sarana Mobilitas Menuju Kampus - Siti Hawa Febriani; Alya Afriliani; Adi Muhammad Syalimul Gaos; Mia Lasmi Wardiyah (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research investigates how students perceive the use of online transport services namely Gojek, Grab, InDriver, and Maxim as their primary means of commuting to campus. App-based transportation has become increasingly vital for addressing urban mobility issues such as traffic congestion, limited parking space, and time constraints. The study adopts a descriptive quantitative method, with data collected through a Likert-scale questionnaire distributed to 20 selected participants. The results reveal a predominantly favorable perception among students, especially regarding convenience, accessibility, efficiency, and safety. All questionnaire items were confirmed to be valid and reliable. Tests for normality and homogeneity showed the data were suitable for further analysis. Moreover, ANOVA results indicated no statistically significant differences in perception among students based on their preferred app. These findings affirm online transportation as a top choice for students to support their academic routines. This study is expected to serve as a valuable reference for developing more adaptive digital transportation services and for universities formulating inclusive and student-centered mobility policies.